Accumulation of flame retardants in paired eggs and plasma of bald eagles. (June 2018) - Guo, Jiehong; Simon, Kendall; Romanak, Kevin; Bowerman, William; Venier, Marta
Abstract: In this study, we measured the concentrations of 58 flame retardants (and related compounds) in bald eagle ( Haliaeetus leucocephalus ) egg and plasma samples from the Michigan. These analytes include polybrominated diphenyl ethers (PBDEs), novel flame retardants (nFRs), Dechlorane-related compounds (Decs), and organophosphate esters (OPEs). A total of 24 paired eaglet plasma and egg samples were collected from inland (IN, N = 13) and the Great Lakes (GL, N = 11) breeding areas from 2000 to 2012. PBDEs were the most abundant chemical group with a geometric mean of 181 ng/g wet weight (ww) in egg and 5.31 ng/g ww in plasma. Decs were barely found in plasma samples, but they were frequently found in eggs (geometric mean 23.5 ng/g ww). OPE levels were comparable to those of PBDEs in the plasma but lower than those of PBDEs in eggs. Dec and PBDE concentrations were significantly higher in GL than in IN ( p  < 0.05). The ratio of egg to plasma concentrations (lipid normalized) varied with chemicals and correlated with the chemical's octanol-water partition coefficient. The lipid normalized bald eagle egg and plasma concentrations from Lake Superior and Huron were one to three orders of magnitude higher than concentrations measured in composite lake trout ( Salvelinus namaycush ) from the same lake, implying that they biomagnify in the environment. Graphical abstract: Image 1 Highlights: Flame retardants in paired egg and plasma of Great Lakes bald eagles. PBDEs were the most abundant chemical group. OPE levels were comparable to those of PBDEs in the plasma. Abstract : Flame retardants are accumulating in bald eagle eggs and plasma. Concentrations of most flame retardants were higher in birds from nests closer to the water. Flame retardants do biomagnify.